PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI (STUDI EMPIRIS PADA SEKTOR CONSUMER PRODUCT AND SERVICE DI BURSA MALAYSIA (BM) TAHUN 2022-2024) - Hariadi, Sugeng; Setyadharma, Queenesya Elvina (POLITEKNIK LP3I JAKARTA, 2026)
This study is intended to determine the effect of CSR and GCG on Firm Value with Profitability as a moderating variable. This study is a descriptive quantitative research type with a quantitative approach. The study uses annual, sustainability, and financial report data of the consumer product and service sector on the Bursa Malaysia website from 12 companies. The sampling method used is purposive sampling, and 36 consumer product and service company data were obtained. The analysis method uses IBM SPSS Statistics 23. The results of this study indicate 1) Corporate Social Responsibility does not have a significant effect on firm value, 2) KM has a significant effect and Institutional Ownership (IO) does not have a significant effect on firm value, 3) Profitability is unable to moderate the effect of Corporate Social Responsibility on Firm Value, 4) Profitability is unable to moderate the effect of GCG on Firm Value.